Structural basis for DNA damage-induced phosphoregulation of MDM2 RING domain - Helge M. Magnussen (Nature Portfolio, 2020)
p53 is an important tumor suppressor protein which is regulated by the E3 ubiquitin ligase MDM2. Here the authors reveal that DNA damage-induced Ser429 phosphorylation of MDM2 serve to boost the activity of MDM2 homodimer by stabilizing the active E2–ubiquitin complex and promote its self-destruction to enable rapid p53 stabilization.